Reduced neutron widths in the nuclear data ensemble: Experiment andtheory do not agree - Koehler P.E. (EPJ Web of Conferences, 2010)
I have analyzed reduced neutron widths (Γ0n) for the subset of 1245 resonances in the nuclear data ensemble (NDE) for which they have been reported. Random matrix theory (RMT) predicts for the Gaussian orthogonal ensemble (GOE) that these widths should follow a χ2 distribution having one degree of freedom (ν = 1) - the Porter Thomas (PT) distribution. Using the maximum-likelihood (ML) technique, I have determined that the Γ0n values in the NDE are best described by a χ2 distribution having ν = 0.80 ± 0.052, which is 3.8 standard deviations smaller than predicted by RMT. I show that this striking disagreement is most likely due to the inclusion of significant p-wave contamination to the supposedly pure s-wave NDE. Furthermore, when an energy-dependent threshold is used to remove the p-wave contamination, ML analysis yields ν = 1.217 ± 0.092 for the remaining data, still in poor agreement with the RMT prediction for the GOE. These results cast very serious doubt on claims that the NDE represents a striking confirmation of RMT.